Moist‐Exposed Burn Ointment Promotes Angiogenesis During Full‐Thickness Wound Healing by Activating the SDF‐1/CXCR4 Axis in a Hyperglycaemic Rat Model. - Zhang, Naili; Fu, Li; Xu, Jiayuan; Gu, Chengxu; Li, Hongxing; Wang, Dong; Liu, Tongshen; Shi, Xueying; Xu, Ning; Qiu, Jun; Ma, Lina (Wound Repair & Regeneration)
The mechanism by which moist‐exposed burn ointment (MEBO) promotes wound healing in diabetic foot ulcers (DFUs) remains unclear. To elucidate this mechanism, we investigated the role of stromal cell‐derived factor‐1 (SDF‐1) in MEBO's ability to enhance ulcer healing and neovascularisation using a full‐thickness wound model in hyperglycaemic rats. On post‐wounding days 3, 7, and 14, the wound healing rates were significantly higher in the MEBO group compared to the model group and Vaseline group (p < 0.05). Additionally, the MEBO group exhibited increased epidermal layer thickness and enhanced collagen fibre deposition relative to the model group and Vaseline group (p < 0.05). Furthermore, the number of CD31‐positive cells and microvascular density (MVD) were significantly elevated in the MEBO group compared to the model group and Vaseline group (p < 0.05). Flow cytometric analysis also demonstrated that the proportion of CD45−, CD34+, and VEGFR2+ cells in the wound area of the MEBO‐treated group was significantly higher compared to the model group and Vaseline group. Expression levels of SDF‐1, HIF‐1α were also markedly higher in the MEBO group compared to the model group and Vaseline group (p < 0.05). Finally, a significant increase in double‐positive CXCR4 and CD31 cells was observed exclusively in the MEBO group of hyperglycaemic rats (p < 0.05). These findings suggest that MEBO therapy promotes angiogenesis and accelerates wound healing through activation of the SDF‐1/CXCR4 axis during wound healing in diabetics.